Peningkatan Praktik Mandiri Ibu dalam Pemantauan Status Gizi Balita melalui Pendampingan Aktivitis Dasa Wisma - Nugraheni S.A; Ronny Aruben; Ike Johan Prihatin; Sari Sari; Etik Sulistyowati (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
The incidence of malnutrition in Indonesia, also in Central Java and Semarang is still high, another problemis the lack of awareness and knowledge of the community including mother on monitoring nutritional status,and there has never been a group of community members who care about nutrition. The aim of this study wastoanalyze changes in maternal attitudes and practices related to child nutrition after Dasawisma’s assistance.The research was carried out in the work area of the Tlogosari Wetan Health Center in Semarang, on the groundsthat the Puskesmas area has a number of Dasa Wisma that have been arranged and also have quite a number ofcases of malnutrition and malnutrition in the last few years, namely between 2.3 to 3.2% of total under five.. Thisresearch was a quasi-experimental study, with a pre and post test one group design. The subjects of the study were110 mothers of toddlers in 35 Dawis work areas, who were selected purposively, the Dawis were provided witha weight-bearing tool and a height gauge. The results showed differences in knowledge and practice regardinginfant nutrition, after being accompanied by Dawis for 1 month (p<0.05), with wilcoxon match paired test. Thisresearch can be used as evidence based practice on the proposed new program in the field of health, Dawis’s assistanceas a program in monitoring the nutritional status of children.